PENGARUH DISIPLIN, KECERDASAN EMOSIONAL DAN KUALITAS KERJA TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN ACEH TAMIANG - Jalaluddin . (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
Increasing times require companies to be able to make decisions in terms of the right strategy in order to compete at an increasingly tight and competitive level of the Agency. In the past year, namely in 2017 there has been a decline in the performance of employees of the Aceh Tamiang District Health Office. This is because the employee's work discipline has decreased by being marked by many employees who arrive late then not only late but the employees like to be provoked by anger in serving the community, this is clearly related to low quality of work and have an impact on the low performance of Aceh Tamiang District Health Office employees compared to other regions. At the same time often employees do not come to work for unclear reasons. Aceh Tamiang District Health Office Jalan Ir. Haji Juanda (Aceh Tamiang Office Complex) Karang Baru Aceh Tamiang District, the sample in this study amounted to 33 people.Y = 45,064 + 2,035X1 + 1,070X2 + 0,234X3 The multiple linear regression equation can be interpreted as follows: If the variable Role Conflict, Job Stress and Organizational Commitment45,064 is equal to zero, then the Organizational Citizenship Behavior will be valued at the unit with a decreasing tendency. If the Role Conflict variable is increased by 1 unit, the Organizational Citizenship Behavior of teachers will increase by 2,035 units. If Job Stress is increased by 1 unit, it will be followed by an increase in Teacher's Organizational Citizenship Behavior by 1,070 units. If the Organizational Commitment is increased by one, it will be followed by an increase in Organizational Citizenship Behavior by 0.234 units